Correlation of teacher extrinsic factors on teacher performance during online learning in Aceh Besar - Maulida Maulida; Hasanuddin Hasanuddin (STAI Hubbulwathan Duri, 2022)
Online learning that is carried out simultaneously affects the world of education. The extrinsic and intrinsic factors of the teacher's personality become one of the problem factors in the learning process. These factors also affect the performance of teachers during the online learning process. This study aims to see the correlation between various extrinsic factors of teachers and teacher performance in online learning. This research activity was carried out from June 2020 to March 2021. The objects in this study were the teachers who teach at SMA N 1 Krueng Baroena Jaya and SMP Abulyatama. Various kinds of problems occur during the online learning process. Extrinsic factors that have a very high correlation value are found in the teacher and student categories. The correlation that shows a positive relationship to teacher problems that affect teacher performance during the online learning process is on the factors of age, income, and employment status.